Amomum glabrum S. Q. Tong (Zingiberace), a new record for the flora of Vietnam - Hung, Nguyen Danh; Chung, Nguyen Thanh; Sam, Ly Ngoc; Huong, Le Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4DO - 10.25073/2588-1140/vnunst.4886, 2019)
Abstract: Amomum glabrum S. Q. Tong (Zingiberaceae), collected from the Provinces in North Central Vietnam (Thanh Hoa province: Xuan Lien Nature Reserve; Nghe An: Pu Mat National Park, Pu Huong and Pu Hoat Nature Resever; Ha Tinh: Vu Quang National Park; Quang Binh: Phong Nha-Ke Bang National Park; Thừa Thiên Huế: Bạch Mã National Park), is reported here as a new record for the flora of Vietnam, which raised the species number of Amomum to 13. A detailed description and coloured photographs are provided along with data on distribution, ecology, phenology, conservation status and notes on the relative species Keywords: Amomum , Amomum glabrum , North Central, Zingiberaceae. References [1] de Boer H., Newman M., Poulsen A.D., Droop A.J., Fér T., Lê T.T.H., Hlavatá K., Lamxay V., Richardson J.E., Steffen K. & Leong-Škorničková J., Convergent morphology in Alpinieae (Zingiberaceae): Recircumscribing Amomum as amonophyletic genus, Taxon 67 (1) (2018) 6–36. [2] Gagnepain F., Amomum. In: Lecomte, P. H., Fl. Indo-Chine 6(1) (1908) 102–117. [3] Pham Hoang Ho, An illustrated Flora of Vietnam 3: 432–461, Youth Publication, Ho Chi Minh City (in Vietnamese). [4] Nguyen Quoc Binh, Classification Research in the Zingiberaceae in Vietnam, Biology PhD., Ha Noi, 2011 (in Vietnamese). [5] V. Lamxay and M.F. Newman, Are vision of Amomum (Zingiberaceae) in Cambodia, Laos and Vietnam, Edinburgh Journal of Botany 69(1) (2012) 99-206. [6] Ly Ngoc Sam & Jana Leong-Skornickova, Amomum cristatissimum (Zingiberaceae: Alpinieae), a new species with echinate fruits from central Vietnam, Nordic Journal of Botany 36(3) (2018) https://doi.org/10.1111/njb.01691. [7] Wu D.L. and Larsen K., Flora of China 24: 347-356. St Louis: Missouri Botanical Garden Press, and Beijing: Science Press, 2000. [8] S.Q. Tong, Some new taxa of Zingiberaceae from Yunnan, Acta Phytotaxonomica Sinica 27(4) (1989) 277–292. [9] W. Roxburgh, Amomum. In: Flora Indica 1 (1820) 37–46. Serampore: Mission Press.